2001
DOI: 10.1186/1471-244x-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in blood perfusion of the anterior cingulate gyri in Anorexia Nervosa Restricters assessed by SPECT image analysis

Abstract: Background: It is possible that psychopathological differences exist between the restricting and bulimic forms of anorexia nervosa. We investigated localized differences of brain blood flow of anorexia nervosa patients using SPECT image analysis with statistic parametric mapping (SPM) in an attempt to link brain blood flow patterns to neurophysiologic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
3
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 15 publications
4
51
3
1
Order By: Relevance
“…In general, neuroimaging studies suggest hyperactivation in regions involved in modulation of visceral responses to salient stimuli during motivation in chronically fooddeprived individuals. This research provides evidence for reduction in activity during rest in prefrontal regions and the anterior cingulate cortex in eating disorders (Delvenne et al, 1999;Naruo et al, 2001;Takano et al, 2001;Wu et al, 1990), with a specific heightened response to presentation of food in the MPFC during hunger (Uher et al, 2004). Our results in normal food motivation also demonstrate a role for the MPFC, a region which showed large increases in response to food before eating in normal weight children and adolescents.…”
Section: Discussionsupporting
confidence: 70%
“…In general, neuroimaging studies suggest hyperactivation in regions involved in modulation of visceral responses to salient stimuli during motivation in chronically fooddeprived individuals. This research provides evidence for reduction in activity during rest in prefrontal regions and the anterior cingulate cortex in eating disorders (Delvenne et al, 1999;Naruo et al, 2001;Takano et al, 2001;Wu et al, 1990), with a specific heightened response to presentation of food in the MPFC during hunger (Uher et al, 2004). Our results in normal food motivation also demonstrate a role for the MPFC, a region which showed large increases in response to food before eating in normal weight children and adolescents.…”
Section: Discussionsupporting
confidence: 70%
“…With regards to functional and morphological changes in the brains of females with AN, some studies have affirmed that the hypoactivity found in the right parietal cortex of these patients (Delvenne, Goldman, Biver, et al, 1997;Delvenne, Goldman, De Maertelaer, & Lotstra, 1999;Delvenne, Goldman, De Maertelaer, et al, 1997;Delvenne et al, 1995;Nozoe et al, 1993Nozoe et al, , 1995 and the hypoactivity found in the anterior cingulated cortex (Kojima et al, 2005;Naruo et al, 2001) reverted after weight gain (Delvenne et al, 1996;Miller et al, 2004), while others found the opposite results (Kojima et al, 2005;Van Kuyk et al, 2009). The cerebral areas most commonly associated with impaired functioning in patients with AN are the parietal cortex, ventromedial prefrontal cortex, gyrus lingualis within the occipital cortex, medial prefrontal cortex, cerebellum, nucleus caudatus, and insula (Grunwald et al, 2001;Sachdev, Mondraty, Wen, & Gulliford, 2008).…”
Section: Brain Structurementioning
confidence: 98%
“…The evidence of the unbalanced ACC activity in mood disorders is extremely wide, for any interest, reader's attention is readdressed to some interesting works [Cotter t al., 2001;Mirza et al, 2004;Thomas et al, 2004;Fornito et al, 2007;Moore et al, 2007;Weis et al, 2007; Bhagwagar et al, 2008; Boes et al, 2008]. Drug abuse disorders [Bouras et al, 2001;Fishbein et al, 2005;Hao et al, 2005;Mohila and Onn, 2005], eating disorders [Naruo et al, 2001;Muhlau et al, 2007;Penas-Lledo et al, 2007], personality disorders [Degos et al, 1993;Takahashi et al, 2002;Haas et al, 2007], and anxiety disorders [Paulus et al, 2004;Butler et al, 2005;Phan et al, 2005;Milad et al, 2007;Bryant et al, 2008;Yucel et al, 2008] have also been associated with disruptions in the ACC. Despite this relevance, there is poor experiment evidence on animals and genetic investigations that focused on this part of the brain with a specific attention devoted to the serotonin receptor 2C.…”
mentioning
confidence: 94%